Design and development of storage management system at FKP - Norzamirah, Kamaruzaman (2013)
This research covers the development of the storage management system in Faculty of Manufacturing Engineering (FKP) laboratory. Concepts of this project are to create one tool storage system to enhance the efficiency of storage management at FKP laboratory. The aims of this research are to develop and analysis before and after implement storage management system at FKP laboratory. There are three phase in this system. Phase I cover the system using the Graphical User Interface (GUI) and Visual Basic (VB) software, Phase II is the interface between the system and hardware using the Peripheral Interface Controller (PIC) microcontroller and solenoids. Phase III is built and implement the system at the hardware. To validate this system, one survey and accuracy test has been made. Feedbacks from the survey shows 97% to 99% users satisfied and highly recommended this system implement at FKP laboratory. This system has been test two hundred times which include two cycles for accuracy test and the results shows the actual movement of the solenoid and yellow Light-emitting Diode (LED) for the first and second drawer. The results show that the system is functional between 97% to 99%. By a proper design, this system can be implementing at FKP laboratory and offers many benefits to the users especially for lecturers and students.